Plasma magnetic cascade multiloop control system design methodology in a tokamak. (June 2019) - Mitrishkin, Yuri V.; Korenev, Pavel S.; Kartsev, Nikolay M.; Kuznetsov, Evgeniy A.; Prokhorov, Artem A.; Patrov, Mikhail I.
Abstract: The paper treats the methodology of the design and analysis of a tokamak plasma magnetic cascade multiloop control system with the example of the Globus-M spherical tokamak (Ioffe Institute, S-Petersburg, Russia) including a set of new features. The methodology covers: plasma equilibrium reconstruction based on the experimental data, derivation of linear plasma models relative to the reconstructed plasma equilibrium taking into account plasma diagnostics methods and equipment, development of a new original model of a thyristor current inverter as an actuator included in the system feedback, original multivariable cascade multiloop structure analysis by Relative Gain Array/ μ -procedures, and design of an H ∞,  multivariable plasma shape control system with adaptation of the magnetic axis position. Graphical abstract: Highlights: Plasma magnetic control system design methodology for elongated & spherical tokamaks. Plasma equilibrium reconstruction & model derivations from tokamak experimental data. Full thyristor current inverter model as a fast actuator for plasma position control. Plasma H ∞ position, current & shape control system with adaptation of magnetic axis. Plasma separatrix transition by feedback control system in the reachability region.